The Effects of Online Learning on Pre-Service Teachers‟ Social Facilitation during Covid-19 Pandemic - Ishmatun Naila; Qaulan Sadida (PROCEEDING UMSURABAYA, 2020)
Abstract. Social facilitation is known as the tendency of people to perform tasks betterwhen it is simple and worse when it is complex, with presence of others. This paper aims to find out whether there is any effect of online learning with pre-service teacher‘s social facilitation during pandemic period or not. Online learning or E-Learning is one of distance learning methods, which nowadays massively used in almost all stages of education, especially during the worldwide-issued ‗work from home‘. The subjects are pre-service elementary teachers in Muhammadiyah University of Surabaya class of 2018. The method used in this research was qualitative description. The data collected from online survey with 45 respondents. Based on the data it was found that 97.7% of respondents conducted online learning, and 58.1% were having trouble understanding the material from online lectures. Material information obtained through online learning was less acceptable to respondents. 96.5% of them experiencing stark difference which more than half (66.3%) are having less enthusiasm to follow the online lectures. 97.7% respondent chose face to face meeting better than online learning. The results showed that they were inclined to do a better job or performance when they had not been alone or felt like they are being monitored and having other friend to share some thought, which could facilitate their behaviours.